2013
DOI: 10.1186/2051-5960-1-57
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Decreased neuroinflammation and increased brain energy homeostasis following environmental enrichment after mild traumatic brain injury is associated with improvement in cognitive function

Abstract: BackgroundPersistent neuroinflammation and disruptions in brain energy metabolism is commonly seen in traumatic brain injury (TBI). Because of the lack of success of most TBI interventions and the documented benefits of environmental enrichment (EE) in enhancing brain plasticity, here we focused our study on use of EE in regulating injury-induced neuroinflammation and disruptions in energy metabolism in the prefrontal cortex and hippocampus. Adult male Wistar rats were used in the study and randomly assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 52 publications
3
56
0
Order By: Relevance
“…14,[22][23][24][25][26][27][28][29][30][31][32]35 Concurrently, many other therapeutic interventions have also been reported to enhance behavioral outcome after TBI using various pre-clinical models; [9][10][11][12][13][14][15][16][17][18] however, most of these strategies have not successfully translated from the bench to the bedside. 19,20 While numerous factors may account for the lack of translation, one salient reason may be the use of single therapies for a disease that exhibits multiple pathophysiological events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,[22][23][24][25][26][27][28][29][30][31][32]35 Concurrently, many other therapeutic interventions have also been reported to enhance behavioral outcome after TBI using various pre-clinical models; [9][10][11][12][13][14][15][16][17][18] however, most of these strategies have not successfully translated from the bench to the bedside. 19,20 While numerous factors may account for the lack of translation, one salient reason may be the use of single therapies for a disease that exhibits multiple pathophysiological events.…”
Section: Discussionmentioning
confidence: 99%
“…57 While we only administered a 5 mg/kg daily dose of MPH, it is not unreasonable to consider that in combination with EE, it may have reduced DA transporter activity to suboptimal levels, such that an overabundance of DA failed to provide additional spatial learning benefits on MWM performance in the TBI+EE+MPH group. While MPH induces therapeutic benefit by primarily targeting DA neurotransmission, EE supports post-injury recovery through multiple pathways or mechanisms including DA system regulation, 55 reductions in pro-inflammatory cytokines, 27 increased neurogenesis, nerve growth factor, and dendritic arborization, [58][59][60][61] or attenuation of medial septal cholinergic cell loss. 28 A recent study demonstrated that rats raised in EE exhibit decreased maximal transport velocity (Vmax) for [ 3 H]DA uptake in medial prefrontal cortex, but increased Vmax for [ 3 H]DA uptake in the orbitofrontal cortex, thus suggesting that EE produces regiondependent long-lasting alterations in DA transporter function via a trafficking-independent mechanism, 62 which may influence the overall effectiveness of MPH treatment when provided concurrently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24][25][26] Likewise, EE has also been shown to confer neurobehavioral and histological benefits in adult male rats after CCI 20,23,[26][27][28][29][30][31][32][33][34] and fluid percussion brain injury. [35][36][37][38][39][40] Recently, the benefits of EE have also been extended to female rats after CCI.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental enrichment (EE), in particular, has been evaluated extensively in adult, and to a much lesser extent, in pediatric rodents as a pre-clinical model of neurorehabilitation. EE consists of expansive accommodations, which include cognitive and social stimulation that results in the reduction of histological damage and enhancement of functional recovery 27 induced by either controlled cortical impact (CCI) 20,23,[26][27][28][29][30][31][32][33][34] or fluid percussion. [35][36][37][38][39][40] Given that the 5-HT 1A receptor agonist buspirone and EE confer recovery in adult rats after brain trauma, the goals of this study were to evaluate the potential efficacy of these therapies alone and in combination after pediatric TBI.…”
Section: Introductionmentioning
confidence: 99%